Effect of Seed Tuber Size on Growth and Yield of Potato (Solanum Tuberosum L.) Variety Desiree in Dadeldhura - Bist, Lokendra; Sharma, Raksha; Thakurathi, Bibek (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
A field study was carried out on potato (Solanum tuberosum L.) variety Desiree to determine the effect of seed tuber size on growth and yield performance in Dadeldhura district in 2023. The experiment was carried out in randomized complete block design (RCBD) using four replications and five treatments. Treatments used were different weighed seed tubers viz.T1:(11-20g),T2:(21-30g), T3:(31-40g), T4:(41-50g), and T5:(51-60g) . The results showed significant effect of the size of seed tubers on the growth and yield of potato. The treatment 51-60g seed tuber proved to be superior in terms of plant height, number of leaves/plant and tuber weight/hill followed by the treatment 31-40g seed tuber. Similarly, at harvest, 31-40g seed tubers yielded maximum number of tubers/hill, number of tuber/m2, total yield, total marketable yield, and average number of stem/hill followed by the treatments 51-60g and 21-30g seed tubers respectively. On the basis of potato tuber grading 21-30g seed tuber yielded bigger sized potato tubers followed by 31-40g and 51-60g respectively. The treatment 31-40g proved to be the best among all the treatments in yielding maximum total yield, total marketable yield and less number of unmarketable tubers. Similarly, the benefit cost ratio obtained from 31-40g seed tuber is significantly higher (3.82) than all other treatments. Hence, 31-40g seed tuber is suggested to farmers for profitable production of potato.